2023
DOI: 10.1111/ddg.14988
|View full text |Cite
|
Sign up to set email alerts
|

S1 Guideline onychomycosis

Abstract: Summary Onychomycosis is a fungal infection of the fingernails and toenails. In Europe, tinea unguium is mainly caused by dermatophytes. The diagnostic workup comprises microscopic examination, culture and/or molecular testing (nail scrapings). Local treatment with antifungal nail polish is recommended for mild or moderate nail infections. In case of moderate to severe onychomycosis, oral treatment is recommended (in the absence of contraindications). Treatment should consist of topical and systemic agents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
(122 reference statements)
0
4
0
1
Order By: Relevance
“…There was a preponderance of home remedy recommendations, including tea tree oil, vinegar, topical cough suppressants, and Listerine ® , in the onychomycosis treatment-related videos, and very limited discussion of antifungals approved by the United States Food and Drug Administration for onychomycosis. Only two of the top ten most frequently recommended treatments on TikTok were in accordance with the most recently published guidelines for the treatment of onychomycosis [6]. We found that physicians uploaded several of the TikTok videos which recommended home remedies and alternative treatments.…”
Section: Discussionmentioning
confidence: 86%
“…There was a preponderance of home remedy recommendations, including tea tree oil, vinegar, topical cough suppressants, and Listerine ® , in the onychomycosis treatment-related videos, and very limited discussion of antifungals approved by the United States Food and Drug Administration for onychomycosis. Only two of the top ten most frequently recommended treatments on TikTok were in accordance with the most recently published guidelines for the treatment of onychomycosis [6]. We found that physicians uploaded several of the TikTok videos which recommended home remedies and alternative treatments.…”
Section: Discussionmentioning
confidence: 86%
“…Out of the available techniques, the most effective testing method is a combined histopathologic examination, where PCR testing as the first test indicates evidence of a fungal invasion in the nail plate and the second test provides pathogen identification. This combination was also recommended as the most effective diagnostic procedure by the German S1 guideline-a guideline reflecting the recommendations of professional medical associations in the field of dermatology and mycology [21]. Due to the distinct possibility of NDMs being present in nails as environmental contaminants or commensal organisms [26], performing a histopathologic examination with PCR not only improves the diagnostic accuracy but also greatly shortens the time-to-treatment initiation, as the traditional fungal culture method requires ≥2 sequential isolations spaced at least 1 week apart [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of PCR diagnosis is the potential inability to differentiate 'true' pathogens from commensal organisms and environmental contaminants, which can thus lead to false positive results. Hence, combining the use of PCR diagnosis with histopathologic examination, especially in the case of suspected NDM onychomycosis, has been suggested as a reliable proxy for true infection with the demonstration of nail plate invasion [21,24]. For samples tested using combined PCR and histopathology (n = 41,284), we assessed the relative proportions of dermatophytes, NDMs, yeasts and mixed detections in PCR-positive and histopathology-positive samples (51.6% [21,290/41,284]), compared to PCR-positive and histopathology-negative samples (6.8% [2796/41,284]).…”
Section: Distribution Of Fungi Groups In Pcr-positive Samples With Or...mentioning
confidence: 99%
See 1 more Smart Citation
“…Микозы являются широко распространенными во всем мире инфекционными заболеваниями, вызываемыми патогенными и условно-патогенными грибами. По разным данным, микозы встречаются примерно у 20-30% населения разного пола и возраста, чаще -у пожилых людей ввиду снижения иммунитета и сопутствующих заболеваний [1][2][3][4][5][6]. Микозы кожи, слизистых оболочек и ногтей составляют до 90% всех грибковых заболеваний человека.…”
Section: Introductionunclassified